The Europeans: FIX&FOXY’s Post-Dramatic Approach to the Classics - Thygesen, Mads (Peripeti, 2023)
How did the staging of The Europeans exploit classics as a tool to intervene and mix in a current historical and political context? The common denominator for the work was European wars as a dramatic focal point. The article discusses how this performance illuminates the seed of FIX&FOXY’s poetics and conceptual thinking from 2005.